Process Evaluation of Project FFAB (Fun Fast Activity Blasts): A Multi-Activity School-Based High-Intensity Interval Training Intervention - Weston, Kathryn L.; Innerd, Alison; Azevedo, Liane B.; Bock, Susan; Batterham, Alan M. (Frontiers in Sports and Active Living, 2021)
Introduction: Over the last decade, research into the impact of school-based high-intensity interval training (HIIT) on young people’s health has markedly increased. Despite this, most authors have focused on the outcomes of their intervention, rather than the process of how the study was conducted. The aim of our study, therefore, was to conduct a mixed methods process evaluation of Project FFAB (Fun Fast Activity Blasts), a school-based HIIT intervention for adolescents. The objectives were to explore study recruitment, reach, intervention dose, fidelity, participants’ experiences, context, and future implementation. Methods: Recruitment was assessed by comparing the number of students who received study information, to those who provided consent. Reach was described as the number of participants who completed the intervention. Dose was reported via the number of HIIT sessions delivered, total exercise time commitment, HIIT exercise time, and session attendance. Post-intervention focus groups were conducted with intervention participants (n=33; aged 14.1 ± 0.3 years; mean ± standard deviation). These discussions explored aspects of intervention fidelity (extent that the intervention was delivered as intended); participants’ experiences of the HIIT sessions; context (exploration of the nuances of school-based HIIT); and ideas for future implementation. Results: Recruitment, reach, and dose data indicate that Project FFAB was largely delivered as planned. Focus group data identified a mismatch between perceived versus prescribed work: rest ratio for the multi-activity HIIT drills. Generally, the HIIT drills were well received; participants often reported they were fun to complete, and the use of heart rate monitors was helpful for interpreting exercise intensity. Some participants stated that greater variety in the HIIT drills would be preferable. The timing and structure of the HIIT sessions that took place outside of physical education lessons received mixed responses. Conclusion: Collectively, our study supports the use of school-based HIIT and provides valuable insights into how such interventions can be implemented. Project FFAB could be modified to account for individuals’ preferences on when the exercise sessions took place. In addition, a wider range of activities could be included, and the prescribed work: rest ratio of the HIIT drills could be better communicated.